Photography as a teaching strategy for teaching and learning about the environment with ninth-grade students at the Cambridge School in Pamplona. A pedagogical experience (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2017)
The educational use of photography in the classroom is beginning to become, for those who use it, a means of persuasion capable of convincing and transforming everyday events. Photography as a visual teaching resource allows for the conception of various educational methods due to its widespread use and means of expression, coupled with the devotion of those who work with it, from researching an environment to representing it through images. Photography is used to develop codes of understanding, interpretation, and transformation of reality to improve the scope of educational processes.